Seroprevalence of hepatitis C, hepatitis B, hiv and syphilis among blood donors at a tertiary care hospital in Mogadishu-Somalia in 2020-2022: a retrospective study - Serpil Doğan; Said Mohamed Mohamud; Ahmed Mohamed Ali; Zerife Orhan; Ahmet Doğan; Rahma Yusuf Haji Mohamud (BMC, 2024)
Abstract Background The safety of blood donation requires screening for transfusion-transmitted infections, including human immunodeficiency virus (HIV), syphilis, hepatitis B virus (HBV) and hepatitis C virus (HCV). This study aimed to determine the seroprevalence of HIV, HBV, HCV and syphilis in blood donors of Mogadishu Tertiary Care Hospital, Somalia from 2020 to 2022. Methods The records of 109,385 blood donors who attended our blood center in Mogadishu-Somalia between 2020 and 2022 were examined retrospectively. Serum samples of donors; HBsAg, anti-HCV, anti-HIV and syphilisscreening tests were studied using the microparticleEnzyme-Linked ImmunoSorbent Assay (ELISA)(Vitros, Ortho-Clinical Diagnostics, U.S) method.The distribution of HBsAg, anti-HCV, anti-HIV and syphilis positivity rates of 109,385 blood donors according to years, gender and age were examined. Kolmogorov Smirnov, Skewness, Kurtosis tests and histogram were used for normality analysis. Chi-squared test (χ2) and Fisher Exact test were used to analyze categorical data. Categorical variables were expressed as frequency (percentage). Analysis of continuous data was performed with the Mann Whitney U test. P < 0.05 value was considered statistically significant. Results HBsAg positivity was found in 0.6% of the donors, anti-HCV positivity in 0.01%, anti-HIV positivity in 0.03% and syphilispositivity in 0.3%. The results showed that among the blood donors, the prevalence of syphilis, HIV, Hepatitis B, and Hepatitis Cwas notably low. Conclusion The prevalence of HBV, HCV, HIV, and syphilis among blood donors in Somalia was found to be quite low. Even if our found seroprevalence rates are low, to guarantee the safety of blood for recipients, strict selection of blood donors and thorough screening of donors' blood using accepted procedures are strongly advised.